Threat, Hazard, Risk and Vulnerability Assessment of Merapi Volcano in Yogyakarta, Indonesia - IM Brunner, I Made (2013)
Merapi, the most active volcano in Indonesia, sits on the northern part of Yogyakarta province where about 1.5 million residents live. In 2006 short after eruption, Merapi area was hit by a 5.9 magnitude earthquakethat destroy the Yogyakarta's natural barrier, known as Geger Boyo.